Fantasy or reality effects of age, premise content, and task organization on children's deductive reasoning - Jocson, Maria Rosanne M.; Lim, Nicholette G (Philippine journal of psychology, 2009)
"The study investigates the effects of age, premise content, and task organization on Filipino children's deductive reasoning. Results indicate that premise content affected children's scores on the reasoning task and patterns of justifications. Further analysis showed that age interacted with premise content to affect children's scores, and also interacted with task organization to affect response justifications. Both 7-year-olds and 4-year-olds showed signs of deductive reasoning ability under constrained conditions. The development of deductive reasoning is discussed in relation to other cognitive processes, and implications are addressed."